Weekend warrior physical activity pattern and common mental disorder: a population wide study of 108,011 British adults - Mark Hamer; Stuart J. H. Biddle; Emmanuel Stamatakis (BMC, 2017)
Abstract Background The dose-response association between physical activity (PA) and mental health is poorly described. We explored cross-sectional associations between physical activity and common mental disorder (psychological distress) in 'weekend warriors' who do all their exercise in one or two sessions per week. Methods Adult participants (n = 108,011, age = 47 ± 17 yrs., 46.5% men) were recruited from general population household-based surveys (Health Survey for England and Scottish Health Survey) from 1994 to 2004. Data were pooled and analyzed using logistic regression models. Moderate to vigorous physical activity (MVPA) was self-reported and psychological distress was measured using the 12 item General Health Questionnaire (GHQ-12). Results Psychological distress (GHQ-12 > 3) was prevalent in 14.5% of the sample. In healthy participants an inverse association between PA and psychological distress was optimal at the PA guideline (150 mins/wk. MVPA or 75 min/wk. Vigorous PA) regardless of whether it was accumulated in one or two bouts per week "Weekend warrior" (odd ratio = 0.68, 95% CI, 0.63, 0.73) or as more frequent daily bouts (odd ratio = 0.68, 95% CI, 0.64, 0.72) in comparison to the inactive reference group. In participants with chronic health conditions an inverse association between PA and psychological distress was also evident at lower doses (one or two sessions of PA a week below PA guideline) (OR = 0.72, 95% CI, 0.68, 0.77). Undertaking vigorous intensity PA as part of the PA guideline conferred additional benefit in women (odds ratio = 0.87, 95% CI, 0.75, 1.00), but not men. Conclusion Mental health benefits may be accrued through different PA patterns, thus individual approaches to prescribing exercise should be promoted.